Design of Water Source Alternative Based on SWAT Model Simulation - Nora Herdiana Pandjaitan; Arif Yusron Afifi; Asep Sapei (The University of Lampung, 2022)
Water shortage problem was often happened in many places in Indonesia. Water availability is very important not only for domestic needs, but also for other activities particularly for agricultural activities. To solve water shortage problem, this study aimed to design a water source alternative. The rain is a free water source and collecting rain in the small dam or reservoir is one of the effective rainwater harvesting technique that can increase water availability. This research was conducted at Sekaran Village and the analysis had done using SWAT (Soil and Water Assessment Tools) model. The planned rainfall and discharge were analysed by 5 years return period to calculate the water potential for reservoir charging. The results of this study indicated that the location of the reservoir was planned in a forest area with a slope of 8-25%, on coordinates 111º38'11.39